2006
DOI: 10.1007/s00232-005-0832-x
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junctions and Cochlear Homeostasis

Abstract: Gap junctions play a critical role in hearing and mutations in connexin genes cause a high incidence of human deafness. Pathogenesis mainly occurs in the cochlea, where gap junctions form extensive networks between non-sensory cells that can be divided into two independent gap junction systems, the epithelial cell gap junction system and the connective tissue cell gap junction system. At least four different connexins have been reported to be present in the mammalian inner ear, and gap junctions are thought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
134
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 98 publications
0
134
0
1
Order By: Relevance
“…12 Recent studies suggested that intercellular communication through GJ is crucial for auditory function. 13,14 In mice, Cx26 and Cx30, apparently the two most abundantly expressed Cxs, are known to co-assemble to form GJ in the cochlea. 15 Mutations of GJB2, which encodes the Cx26 protein, and GJB6, which encodes the Cx30 protein, are implicated in cases of inherited nonsyndromic hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…12 Recent studies suggested that intercellular communication through GJ is crucial for auditory function. 13,14 In mice, Cx26 and Cx30, apparently the two most abundantly expressed Cxs, are known to co-assemble to form GJ in the cochlea. 15 Mutations of GJB2, which encodes the Cx26 protein, and GJB6, which encodes the Cx30 protein, are implicated in cases of inherited nonsyndromic hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction of gap junctions can induce a high incidence of hearing loss [1]. For a long time, researchers have hypothesized that the inner ear gap junctions mediate K + transport back to the endolymph [2][3][4][5][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting cells in the cochlea provide physical support and nutrition to hair cells and also play an important role in the maintenance of cochlear ionic homeostasis [1,2]. It has been hypothesized that supporting cells in the cochlea like glia cells in the brain absorb or sink K + ions, which hair cells release during mechano-electrical transduction, and transport them back to the endolymph via intracellular gap junctional communication [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Several different connexin sub-units were reported to be expressed in the mammalian inner ear. 3 Mutations in these genes were responsible for various types of ARNSHI (Hereditary hearing loss homepage: http://webhost.ua.ac.be/hhh/). The second candidate gene screened was FXYD4.…”
Section: Discussionmentioning
confidence: 99%